In search of sustainable successful traders in times of crisis - Kleinlogel, Emmanuelle; Schmid Mast, Marianne; Frauendorfer, Karl; Gutsche, Robert; Rif, Alexandru (Management international / International Management / Gestiòn Internacional, 2024)
In recent decades, recurring global crises have stemmed from management shortcomings in various organizations, particularly within the financial sector (e.g., the 2000 stock market crash, 2011 UBS rogue trader scandal). Excessive risk-taking attitudes by traders and investment and risk managers are tied to these crises. Identifying high performance individuals who are also responsible from a societal stance is a challenge. In this paper, we tackle this issue by investigating the personality traits that characterize responsible and successful traders to improve personnel selection procedures with cross-cultural applicability. Our findings reveal that being conscientious and intelligent while at the same time being inclined to take financial risks, are significantly associated with responsible trading performance.